Dispersion-enhanced solute transport in a cell-seeded hollow fibre membrane bioreactor - Pearson, N; Shipley, R; Waters, S; Oliver, J (Springer Netherlands, 2015)
We present a matched asymptotic analysis of the fluid flow and solute transport in a small aspect ratio hollow fibre membrane bioreactor. A two-dimensional domain is assumed for simplicity, enabling greater understanding of the typical behaviours of the system in a setup which is analytically tractable. The model permits analysis related to Taylor dispersion problems, and allows us to predict the dependence of the mean solute uptake and solute exposure time on key parameters such as the inlet fluid fluxes, porous membrane porosity and cell layer porosity and width, which could be controlled or measured experimentally.